PENGARUH NISBAH BAGI HASIL DEPOSITO MUDHARABAH TERHADAP MINAT NASABAH BERINVESTASI PADA BANK SYARIAH MANDIRI - Jamaludin; Heri Gunawan; Sholikul Hadi (Al-Mubin, 2019)
Profit sharing is a system that includes profit sharing between the investor and the manager of the profit sharing fund. Profit sharing is a form of return (acquisition of business activities) from an investment contract, from time to time, uncertain and uncertain, the size of the recovery depends on business results that actually occur in Islamic banks, the ratio is a mechanism for sharing the share of business profits for each party conducting joint business activities, the amount of which is determined based on an agreement, the ratio is the profit which must be stated in percentage form between the two parties. , not stated in a certain rupiah nominal value. This ratio reflects the compensation entitled to receive by both parties who are bermudharabah. This study aims to examine the effect of the profit sharing ratio on mudharabah deposits on customers' interest in investing in Bank Syariah Mandiri, Branch Tajur Bogor. This research method is a quantitative survey, with a purposive sampling method with a questionnaire to 75 customers. Data analysis techniques are validity test, reliability test, classic assumption test (normality test, multicolonierity test, heteroscedasticity test, autocorrelation test) and hypothesis testing using (partial test, coefficient of determination and simple linear regression equation test) with the help of Statistical Package for the Social Sciences (SPSS). The results showed that the profit sharing ratio of mudharabah deposits partially or separately had a positive and significant effect on customer interest in investing in Bank Syariah Mandiri, Branch Tajur Bogor. It can be concluded that the motive of the customer to save his assets in the bank is not only to make it easier to make payment transactions and because of the level of security of the assets, but he wants to get profit (profit sharing)